2022
DOI: 10.1177/21514593221080341
|View full text |Cite
|
Sign up to set email alerts
|

Current Practice of Italian Association of Revision Surgery Members in the Treatment of Unified Classification System Type B Periprosthetic Femoral Fracture Around Hip Arthroplasty: A Cross-Sectional Survey

Abstract: Introduction Periprosthetic femoral fracture around hip arthroplasty are growing in the world, nevertheless management and treatment options for fractures “around the stem” are still debated due to lack of high-level studies. Materials and method A 85-item survey were fill out by 40 Italian Orthopedic Surgeon member of SIOT (Società Italiana di Ortopedia e Traumatologia) and AIR (Associazione Italiana Riprotesizzazione) to assess their current opinion in the management of type B periprosthetic femoral fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…The Vancouver classification system, which is commonly employed to guide treatment choices, demonstrated a satisfactory degree of agreement among observers for Unified Classification System (UCS) type B fractures (k=0.76). Nonetheless, the differentiation between B1 and B2 fractures presents difficulties as a result of constraints in preoperative X-ray assessments (k=0.64) [16].…”
Section: Discussionmentioning
confidence: 99%
“…The Vancouver classification system, which is commonly employed to guide treatment choices, demonstrated a satisfactory degree of agreement among observers for Unified Classification System (UCS) type B fractures (k=0.76). Nonetheless, the differentiation between B1 and B2 fractures presents difficulties as a result of constraints in preoperative X-ray assessments (k=0.64) [16].…”
Section: Discussionmentioning
confidence: 99%
“…The Vancouver classification system, which is commonly employed to guide treatment choices, demonstrated a satisfactory degree of agreement among observers for UCS type B fractures (k=0.76). Nonetheless, the differentiation between B1 and B2 fractures presents difficulties as a result of constraints in preoperative X-ray assessments (k=0.64) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, several studies revealed that revision surgery was the most common approach for Type B2/B3 fractures, while simple fixation prevailed as the predominant strategy for Type B1/C fractures. 90 , 91 , 92 Furthermore, Thomas et al . reported that monoblock tapered stems can be an acceptable modality in the treatment of Type B2 fractures, while Capone et al .…”
Section: The Modification For Vcs —The Unified Cla...mentioning
confidence: 99%
“…90-92 Furthermore, Thomas et al reported that monoblock tapered stems can be an acceptable modality in the treatment of Type B2 fractures, while Capone et al indicated that for Type B2 and B3 fractures, revision with modular stems is preferable to monoblock stems. 91,93 A multicenter study has indicated that for Type B fractures around cemented polished taper-slip femoral components, ORIF is associated with lower reoperation rates, shorter waiting times for surgery, reduced transfusion needs, and lesser demands for critical care compared to revision surgery. 94 Conversely, research by Scalici et al found that patients with Type B and C fractures undergoing revision surgery had better functional outcomes than those treated with ORIF.…”
Section: The Basis Factors For the Classification Systems For Ppffmentioning
confidence: 99%
See 1 more Smart Citation